THE INFLUENCE OF SOCIAL CAPITAL AND ECONOMIC POTENTIAL ON THE PRODUCTIVITY AND COMPETITIVENESS: CASE STUDY BUMDES IN BADUNG REGENCY - Putra Yasa, I Made; Purbadharmaja, Ida Bagus Putu (Jurnal REP (Riset Ekonomi Pembangunan), 2024)
The competitiveness of Village-Owned Enterprise (BUMDes) act like a form of excellence or ability possessed by a business in producing a product that can meet the criteria of excellence in the market and can run sustainably and sustainably. The purpose of this study is to analyze the effect of social capital, economic potential, and productivity on competitiveness. To analyze the indirect effect of social capital and economic potential on the competitiveness of BUMDes through productivity. The method of determining the sample uses a saturated sample. The number of samples in this study was 46 BUMDes. Data collection methods used questionnaires, documentation, and in-depth interviews. The data analysis technique used partial least square. The results of research on social capital and economic potential have a positive and significant impact on the productivity of BUMDes. Social capital, economic potential, and productivity have a positive and significant impact on the competitiveness of BUMDes. There is an indirect effect of social capital and economic potential on the competitiveness of BUMDes through productivity.